The potency of kitolod leaves (Hipobroma longiflora) as traditional medicine for conjunctivitis during the COVID-19 pandemic: a brief review - Yuliana; Ni Made Ersi Dwitami Barsua; Made Wulan Virgioni Putri; I Nyoman Satya Mahayana Putra (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
During the coronavirus disease 2019 (COVID-19) pandemic, most activities have transformed into digital ones, including computer usage. The digital screen on the computer has blue light radiation which can activate inflammatory cytokines of the eye surface and cause various disorders including includes conjunctivitis. Kitolod leaves (Hippobroma longiflora) have been used traditionally to treat conjunctivitis. This paper aimed to describe the potency of kitolod leaves for conjunctivitis. This is a narrative literature review using publications gathering from PubMed and Google Scholar published since 2013 with exclusion criteria were the animal studies. The keywords of COVID-19 pandemic, blue light, conjunctivitis, H. longiflora, traditional therapy were used. Boolean logic